The Provision of Unsecured Micro Business Loans at Bank BKC Susukan Branch Office of Cirebon Regency - Carki Carki; Jawade Hafidz; Nanang Sri Darmadi (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
Micro Business Credit is financing for Micro, Small, Medium Enterprises (MSMEs) in the form of providing working capital supported by guarantee facilities for productive businesses. Bank BKC Susukan Branch of Cirebon Regency is a Regional Rural Bank in addition to conventional commercial banks such as BNI, BTN, Bank Mandiri, Bukopin, Mandiri Syariah Bank which is trusted by the government to distribute business loans. The phenomenon that occurs, through this Micro Business Credit, the borrower does not need to provide collateral to the bank because this credit is a loan without collateral and has been guaranteed by the government. This does not mean that if the program has been borne by the government, this program can run smoothly and in accordance with the desired expectations. Basically, this loan is one of the BANK BKC program for the Susukan Branch Office where the bank is the place for micro business credit to be distributed to the public, of course with the internal policies and requirements of the bank. Therefore, unsecured credit is facilitated by this bank because it is basically micro-enterprises that drive the economy of the area, therefore with the aim of helping the micro community, banks also benefit from good economic movements, so that bank activities in the bank's business will be good because with the existence of a given credit means that the bank earns a relatively high interest considering that the loan is given without any collateral.